EFFECT OF ORGANIC MEDIA AND BIOLOGICAL FERTILIZATION ON THE VEGETATIVE AND FLORAL GROWTH AND SOME QUALITATIVE TRAITS OF TWO ROSE HYBRIDS. - Fadel J. Kazem, Fadel J. Kazem; Nawal M. Alwan, Nawal M. Alwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The study was conducted to study the impact of rice straw and sugarcane bagasse residues, as well as biofertilization (Azospirillum and Trichoderma), on the growth, flowering, and quality of two hybrids of roses. The experiment included three main factors: the varieties (Pink-Martini and Brighton), five organic media factors including rice straw at two levels (2 and 4 kg/m2, sugarcane bagasse residues at two levels (2 and 4 kg/m2), in addition to a control treatment without additives. The third factor represented biofertilization by adding Azospirillum and Trichoderma. The results indicated that the applied treatments led to better results in most of the studied characteristics. Overall, the results showed that using rice straw or sugarcane bagasse residues as a source of organic fertilizers, along with biofertilization, improved the growth, flowering, and quality of roses. The results also showed that the triple interaction between the treatments exhibited superiority, with treatment A2B1C1 showing the highest percentage of phosphorus (0.38%), flower count (11.25 flowers per plant), and treatment A2B1C2 in the floral stem diameter and its longevity on the plant (3.57 cm2 and 28.33 days). The study recommends the use of the Brighton hybrid with 4 kg of rice straw and biofertilizer (Azospirillum) to achieve optimal overall growth, flowering, and quality. This combination yielded the best results in the study.